Development of gas chromatographic mass spectrometry-pattern recognition method for the quality control of Korean Angelica - Piao, Xiang-Lan; Park, Jeong Hill; Cui, Han; Kim, Dong-Hyun; Yoo, Hye Hyun (ELSEVIER SCIENCE BV, 2007)
This paper describes gas chromatographic/mass spectrometry (GC/MS)-pattern recognition methods for the quality control of Korean Angelica. A total of 57 Angelicae radix samples, including Angelica gigas (Korean origin), A. sinensis (Chinese origin) and A. acutiloba (Japanese origin), were analyzed by GC/MS, with a principal component analysis (PCA) subsequently applied to 10 common peaks selected from each chromatogram. As a result, the samples were clustered according to their origins on the PC score plot. The loading plot revealed that decursin and decursinol angelate were the most contributive principles distinguishing Korean samples from Chinese and Japanese samples, In addition, a discriminant model was developed for classification of the Angelicae radix, using a discriminant analysis (DA), and validated with a training set (three from A. gigas, four from A. sinensis, and three from A. acutiloba). All samples tested were successfully classified according to their species origin. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; LIGUSTICUM-CHUANXIONG; MEDICINAL-PLANTS; IDENTIFICATION; COUMARIN; QUANTIFICATION; COMPONENTS; SINENSIS; DECURSIN; DANGGUI